Análise da função diafragmática após a intervenção da estimulação elétrica transcutânea em pacientes tetraplégicos - Santos, Ana Paula Coelho Machado dos (2009)
The tetraplegia is an injury in the spinal cord that compromises the motor and sensitive systems commanded by the spinal cord below of that damage level. Respiratory muscles are compromises too. In complete injuries, motor and sensorial function completely damaged. In the incomplete or partial injuries, motor and sensitive function occurs, but no recovery pattern is known. The electric stimulation is used nowadays for respiratory induction. In this work, 10 tetraplegic patients had been evaluated, both gender, ages range from 18 to 48 years, during 10 sessions where anamneses were applied. Vital signals motor respiratory disfunction, and injury level were evaluated. The system of synchronized electrostimulation was applied using two methods: the first one with manual synchronization; FESSM; and the second one, using the MD2, with automatic synchronization. The muscular function of the Diaphragm was evaluated before and after the applications of electrostimulation. The comparative analysis between the two methods, had shown better results after the intervention with equipment I regarding the parameters and vital signs of manovacuometry. With the intervention of equipment II, it was observed better results in the pulse parameters and degree of dyspnea. The equipment I had shown satisfactory results for the function of the digestive system, especially in patients with incomplete spinal cord injury.